Assessing The Role of Psyllium Husk for Sensory Impact on Taste, Aroma and Texture of Rice Krispy Cereal Bar Snack - Angrainy, Hanny; Chandra, Thalia; Tjahjono, Novita; Kurniawan, Maycella Sheren (Indonesia International Institute for Life Sciences, 2024)
The cereal bars market has experienced significant growth due to the rise of the